The Asymmetric Effect of Oil Price Uncertainty on Corporate Investment in China: Evidence From Listed Renewable Energy Companies - Cao, Hong; Sun, Pengfei; Guo, Litian (Frontiers in Energy Research, 2020)
This study evaluates the asymmetric impact of international oil price uncertainty on firms’ investment in China using a sample of listed renewable energy firms over the period 2000-2017 based on the fixed effect model. The empirical results show that the coefficient of oil price uncertainty on corporate investment is significantly negative, and it significantly affects corporate investment efficiency. Further, it reveals that from the total sample, no matter whether the oil price rises or falls, or the oil price is higher or lower, there is no asymmetry. However, after grouping companies according to the average investment opportunity, we found that for companies with better investment opportunities, the effect of oil price uncertainty on investment is asymmetric, since the coefficient of the the interaction term between high oil prices and oil price uncertainty is significant positive. It also shows that increasing oil price uncertainty will reduce the investment efficiency of companies with poor investment opportunities, and the results of regression using inefficient investment as the explanatory variable also confirm this. Sale capital ratio, firm size, firm age and administrative expense ratio are also vital factors in determining renewable energy firms’ investment. This study has important policy implications for both government and enterprise.